Outcome after neoadjuvant chemoradiation and correlation with nutritional status in patients with locally advanced pancreatic cancer - Naumann, P.; Habermehl, D.; Welzel, T.; Debus, J.; Combs, S. E. (Strahlentherapie und Onkologie, 2013)
Background: Cancer patients commonly suffer from weight loss since rapid tumor growth can cause catabolic metabolism and depletion of energy stores such as abdominal fat. In locally advanced pancreatic cancer this is even more pronounced due to abdominal pain, fatigue, nausea or malnutrition. In the present article, we quantify this frequently observed weight loss and assess its impact on outcome and survival. Methods: Data on demographics, biometrics, toxicity and survival were collected for the last 100 patients treated with neoadjuvant chemoradiation for locally advanced pancreatic cancer at our department (45.0 Gy and boost up to 54.0 Gy plus concurrent and subsequent gemcitabine), and the subcutaneous fat area at the umbilicus level was measured by computer tomography before and after chemoradiation. Results: After chemoradiation, patients showed a highly statistically significant weight loss and reduction of the subcutaneous fat area. We could determine a very strong correlation of subcutaneous fat area to patient BMI. By categorizing patients according to their BMI based on the WHO classification as slender, normal, overweight and obese, we found improved but not statistically significant survival among obese patients. Accordingly, patients who showed less weight loss tended to survive longer. Conclusions: In this study, patients with pancreatic cancer lost weight during chemoradiation and their subcutaneous fat diminished. Changes in subcutaneous fat area were highly correlated with patients' BMI. Moreover, obese patients and patients who lost less weight had an improved outcome after treatment. Although the extent of weight loss was not significantly correlated with survival, the observed trend warrants greater attention to nutritional status in the future. © 2013 Springer Heidelberg Berlin.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cachexia; Locally advanced pancreatic cancer; Neoadjuvant chemoradiation; Nutritional status; Obesity; Subcutaneous fat